VEGETATIVE DEVELOPMENT PREDICTIVE PARAMETERS OF MUTAGENESIS AND ANTIMUTAGENESIS IN Aspergillus nidulans - Guidoti, David Teixeira; Guidoti, Daniela Granella Gomes; Rocha, Carmem Lúcia de Mello Sartori Cardoso da (SaBios-Revista de Saúde e Biologia, 2020)
Aspergillus nidulans (Ascomycota) has been used as a model organism in research on eukaryote genetics for more than 50 years. Its sophisticated mechanism for regulating the expression of genes that control vegetative development make the analysis of conidial germination a relevant tool in assessing the possible effect of different factors on gene regulation mechanisms. Bromelain is a complex mixture of proteolytic and nonproteolytic substances, obtained from the stem and immature fruit of the pineapple plant (Ananas comosus). Its biological activities include anti-inflammatory, antithrombotic, fibrinolytic, anticancer and pro-apoptotic effects. The present study aimed to apply survival and germination tests as a preliminary analysis to assess the cytotoxic, mutagenic and antimutagenic potential of candidate agents. To that end, different concentrations of commercial bromelain were used as the test substance and ultraviolet (UV) light as a mutagenic agent. Bromelain showed no toxicity to the spore viability assay or mutagenicity in the germination test. However, a pro-apoptotic effect was observed in the treatment without UV light when the number of cell deaths increased in concentrations of 2.5 and 25 μg.mL-1, two times higher than the negative control. In addition, bromelain exhibited an antimutagenic effect in the germination test in the presence of UV light, halving the percentage of malformed conidia in relation to the positive control. The results indicated that survival and germination testing of A. nidulans conidia can be used as complementary tools for screening substances with possible cytotoxic, mutagenic or antimutagenic potential, since the combined analysis of survival, mortality and malformations allows inferences to be made regarding damage or protection by repair and/or apoptosis PARÂMETROS DE DESENVOLVIMENTO VEGETATIVO PREDITIVOS DE MUTAGÊNESE E ANTIMUTAGÊNESE EM Aspergillus nidulans Aspergillus nidulans (Ascomycota) é um organismo modelo empregado há mais de 50 anos em estudos de genética dos eucariotos. Por possuir um sofisticado mecanismo de regulação da expressão de genes que coordenam o desenvolvimento vegetativo, a análise da germinação de conídios é uma ferramenta a ser considerada para avaliar o possível efeito de diversos fatores sobre os mecanismos de regulação gênica. A bromelina é uma complexa mistura de substâncias proteolíticas e não proteolíticas, obtida do caule ou de frutos imaturos de abacaxi (Ananas comosus). Suas atividades biológicas descritas incluem efeito anti-inflamatório, antitrombótico, fibrinolítico, anticâncer e pró-apoptótico. O presente trabalho propôs a utilização do ensaio de sobrevivência e de germinação de conídios de A. nidulans, como avaliação preliminar, para verificar o possível potencial citotóxico, mutagênico e antimutagênico de agentes candidatos. Para isso, foi utilizado diferentes concentrações de bromelina comercial, como substância teste, e a luz ultravioleta (UV) como agente mutagênico. A bromelina não mostrou toxicidade no ensaio de sobrevivência, nem mutagenicidade no ensaio de germinação. No entanto, apresentou efeito pró-apoptótico no tratamento sem luz UV, ao aumentar o número de mortos nas concentrações 2,5 e 25 μg mL-1, valor duas vezes maior que o do controle negativo. Além disso, a bromelina mostrou efeito antimutagênico no ensaio de germinação na presença de luz UV, reduzindo pela metade a porcentagem de conídios malformados, em relação ao controle positivo. Os resultados do presente trabalho indicaram que a análise de sobrevivência e o ensaio de germinação de conídios de A. nidulans constituem ferramentas complementares na triagem de substâncias com possível potencial citotóxico, mutagênico e/ou antimutagênico, uma vez que a análise associada de sobrevivência, mortalidade e malformações, permite inferir sobre danos ou proteção por reparo e/ou apoptose.